Social Media Interventions Strengthened COVID-19 Immunization Campaign - Di Mauro, Antonio; Di Mauro, Federica; De Nitto, Sara; Rizzo, Letizia; Greco, Chiara; Stefanizzi, Pasquale; Tafuri, Silvio; Baldassarre, Maria Elisabetta; Laforgia, Nicola (Frontiers in Pediatrics, 2022)
Background: Since The Italian Medicines Agency - AIFA has recommended COVID-19 vaccine Comirnaty in children aged 5 to 11, the immunization campaign faced the vaccine hesitancy in parents. Social media are emerging as leading information source that could play a significant role to counteract vaccine hesitancy, influencing parent’s opinions and perceptions. Our aim was to evaluate the coverage of COVID-19 vaccine Comirnaty in a cohort of children aged 5 to 11 whose families have been counselled to use Social Media to counteract vaccine hesitancy. Methods: All parents of children aged 5 to 11 in a primary care setting were instructed by their paediatrician to get correct information about COVID-19 vaccine from a Facebook page. Active calls to vaccinate children was also scheduled through messaging service Pediatotem and Whatsapp. Vaccination rates of children were assessed with an electronic database and compared to both regional and national children. Results: Coverage of 277 children aged 5 to 11 were analysed from December 16, 2021 to January 31, 2022. 62.4% (173/277) of enrolled children received the 1st dose of COVID-19 vaccine Comirnaty and 39.7% (110/277) the 2nd dose. Coverage rates were higher compared both to regional population (1st dose: 48,8% , 2nd dose: 24,6% ;p = 0.001) and national population (1st dose: 32,1% , 2nd dose: 13,8% ; p < 0.001). Conclusion: Increasing vaccine confidence using Social Media interventions have a positive impact on vaccination acceptance of parents.